Building Humanistic and Inclusive Public Policy: A Public Administration Perspective toward the 2030 SDGs - Isnaeni Yuliani; Syarifa Khasna; Jayanti Armida Sari (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2026)
This study aims to explore how a humanist and inclusive approach in public administration can improve the effectiveness of public policies in achieving the 2030 Sustainable Development Goals (SDGs), specifically SDG 5 (Gender Equality), SDG 10 (Reducing Inequality), and SDG 16 (Peace, Justice, and Strong Institutions). This study uses a descriptive-analytical qualitative approach based on a literature review and analysis of policy documents. Various international and national policy frameworks such as the United Nations 2030 Agenda, the Indonesian RPJMN 2020-2024, and relevant ministerial regulations are reviewed to identify values and practices that support humanist and inclusive governance. This research also uses theoretical perspectives from modern public administration and inclusive governance studies. This study found that integrating human values, empathy, and social participation into public policy processes increases policy legitimacy, strengthens social cohesion, and enhances distributive justice. In addition, the transformation of the role of the bureaucracy from mere implementers to social facilitators contributes to the creation of a more equitable and sustainable governance system. This study is conceptual and limited to secondary data analysis; it does not include empirical field research or quantitative validation. This research is particularly relevant for policymakers, public administrators, and academics interested in sustainable and equitable development. The novelty of this research lies in the integration of the principles of humanism and inclusivity into the theoretical and practical discourse of public administration, offering a human-centered framework to achieve the 2030 SDGs through transformative governance. AbstractStudi ini bertujuan untuk mengeksplorasi bagaimana pendekatan humanis dan inklusif dalam administrasi publik dapat meningkatkan efektivitas kebijakan publik dalam mencapai Tujuan Pembangunan Berkelanjutan (SDGs) 2030, khususnya SDG 5 (Kesetaraan Gender), SDG 10 (Mengurangi Ketidaksetaraan), dan SDG 16 (Perdamaian, Keadilan, dan Lembaga yang Kuat). Studi ini menggunakan pendekatan kualitatif deskriptif-analitis berdasarkan tinjauan pustaka dan analisis dokumen kebijakan. Berbagai kerangka kebijakan internasional dan nasional seperti Agenda 2030 Perserikatan Bangsa-Bangsa, RPJMN Indonesia 2020-2024, dan peraturan menteri terkait ditinjau untuk mengidentifikasi nilai-nilai dan praktik yang mendukung tata kelola humanis dan inklusif. Penelitian ini juga menggunakan perspektif teoritis dari studi administrasi publik modern dan tata kelola inklusif. Studi ini menemukan bahwa mengintegrasikan nilai-nilai kemanusiaan, empati, dan partisipasi sosial ke dalam proses kebijakan publik meningkatkan legitimasi kebijakan, memperkuat kohesi sosial, dan meningkatkan keadilan distributif. Selain itu, transformasi peran birokrasi dari sekadar pelaksana menjadi fasilitator sosial berkontribusi pada terciptanya sistem pemerintahan yang lebih adil dan berkelanjutan. Studi ini bersifat konseptual dan terbatas pada analisis data sekunder; tidak mencakup penelitian lapangan empiris atau validasi kuantitatif. Penelitian ini sangat relevan bagi para pembuat kebijakan, administrator publik, dan akademisi yang tertarik pada pembangunan berkelanjutan dan adil. Kebaruan penelitian ini terletak pada integrasi prinsip-prinsip humanisme dan inklusivitas ke dalam wacana teoretis dan praktis administrasi publik, menawarkan kerangka kerja yang berpusat pada manusia untuk mencapai SDGs 2030 melalui tata kelola transformatif.